Strategy Management Using SWOT Analysis on Patient Satisfaction Rate in Dr. Sardjito Central General Hospital - Rochana Ruliyandari (Universitas Muhammadiyah Yogyakarta, 2019)
Dr. Sardjito Central General Hospital is a class A teaching hospital which is a DIY and South Central Java referral hospital. This hospital still has a disadvantage in terms of patient satisfaction, where it has not met the standards set by national standards ≥85% and the target of medium-term hospitals in 2017 is 90% but the achievement of Dr Sardjito General Hospital is 81.66%. Deficiencies in terms of these services can be a weakness and even a threat to Dr. Sardjito General Hospital. Therefore, to analyze these problems using a strategy using the SWOT analysis method. The method used is descriptive. The type of data used secondary data, namely from records or company documentation and scientific publications. Obtained a total FSI score of 3.35 means greater strength than weakness. The total FSE score of 3.65 means that the opportunity was greater than the threat. The strategy that can be used based on the SWOT analysis is strength and opportunity.